2022
DOI: 10.1111/faam.12337
|View full text |Cite
|
Sign up to set email alerts
|

Digital affordances and remote public audit practice

Abstract: As public sector organizations are undergoing a digital transformation, public auditing is increasingly relying on technology to enable it to collect and analyze large amounts of data. We analyze how the introduction and development of digital artifacts in a governmental audit setting end up affording audit practices. Focusing on the introduction of computer‐assisted audit tools and techniques (CAATTs) developed by Courts of Accounts in Brazil, our findings indicate that the digital infrastructure maintained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Following a path dependence approach, in the presence of contingency and self-reinforcement patterns leading to the lock-in effect (Vergne and Duran, 2010), the legacy systems are ultimately maintained due to the increasing returns of usage linked to the investment in supplementary systems that form the digital Audit digitalisation and local governments infrastructure. In the case under analysis, the core scripts of Courts of Accounts' DCS were written up in the late '90s and early 2000s (Aquino et al, 2022a), and new auditing modules have been connected to the legacy systems aiming to increase its usability (Aquino et al, 2022b). Thus, Courts of Accounts' DCSs are complex systems built up upon costly investments over time, and their development follows a path-dependent trajectory (Aquino et al, 2022a).…”
Section: Effects Of Emergent Audit Digital Infrastructures In Local G...mentioning
confidence: 99%
See 3 more Smart Citations
“…Following a path dependence approach, in the presence of contingency and self-reinforcement patterns leading to the lock-in effect (Vergne and Duran, 2010), the legacy systems are ultimately maintained due to the increasing returns of usage linked to the investment in supplementary systems that form the digital Audit digitalisation and local governments infrastructure. In the case under analysis, the core scripts of Courts of Accounts' DCS were written up in the late '90s and early 2000s (Aquino et al, 2022a), and new auditing modules have been connected to the legacy systems aiming to increase its usability (Aquino et al, 2022b). Thus, Courts of Accounts' DCSs are complex systems built up upon costly investments over time, and their development follows a path-dependent trajectory (Aquino et al, 2022a).…”
Section: Effects Of Emergent Audit Digital Infrastructures In Local G...mentioning
confidence: 99%
“…As seen, the emergent public audit digital infrastructure might shape the way information is being registered and reported by audited organisations. Indeed, one concern arising from the widespread usage of DCSs is that local governments may lose autonomy due to the standards and norms enforced by the emerging digital infrastructure (Aquino et al, 2022b). When local governments perceive a loss of autonomy, they may resort to decoupling the activities related to the audit process from the core organisational processes in placeaffecting their performance (Oliver, 1991;Power, 1999) and overall effectiveness of public financial management reforms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We define audit success when the audit exhibits high audit quality, high audit efficiency, and high auditors' job satisfaction. Existing studies have reported variances in the audit quality (Gong et al, 2022; Handoko & Lindawati, 2021; Jin et al, 2022; Thompson, 2022), audit efficiency (Choudhury et al, 2021; Farcane et al, 2023), and auditors' satisfaction (Aquino et al, 2022; Grant et al, 2018; Rani et al, 2018) from on‐site audits to remote audits. To answer the critical question of how to ensure audit quality and efficiency and retain audit employees in the remote auditing environment, research efforts are needed to systematically understand what leads to variances in audit quality, audit efficiency, and auditors' job satisfaction.…”
Section: Introductionmentioning
confidence: 99%